Active Families in the Great Outdoors: a program to promote family outdoor physical activity. Issue 3 (3rd July 2017) - Flynn, Jennifer I.; Bassett, David R.; Fouts, Hillary N.; Thompson, Dixie L.; Coe, Dawn P.
ABSTRACT: This study evaluated a 4-week program to increase the time families spent engaging in outdoor activity. Parents were provided strategies to increase family outdoor activity and locations to be active. Sixteen families completed the program. Duration and number of family outdoor activity bouts per week, type of activities, locations, and family member attendance were measured using logs. Pre/post surveys were conducted to determine the usefulness of providing educational resources and maps. Compared to baseline (216.1±127.3 min/week), family outdoor activity for weeks 1 (316.1±180.2 min/week), 2 (351.1±209.1 min/week), and 4 (317.5±186.8 min/week) were significantly greater at follow-up. At follow-up, parents reported increased regular exercise and encouragement for their child to be active. Children reported adults engaged in physical activity with them and increased transportation to places to be active. This novel program increased family outdoor activity levels and contributes to limited research on strategies to increase outdoor activity in youth.